Analysis Comparison Of Earnings Between Farmer of Coffee Which Processing by Using Pulper Coffee and With Way of Traditional in Tangga Rasa Village Sikap Dalam Sub District Empat Lawang District - Resdianto, Tri; Batubara, Marli; Iswarini, Harniatun (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2015)
Analysis Comparison Of Earnings Between Farmer of Coffee Which Processing by Using Pulper Coffee and With Way of Traditional in Tangga Rasa Village Sikap Dalam Sub District Empat Lawang District". This research aim to know the background of coffee farmer which using appliance of pulper coffe in Tangga Rasa Village Sikap Dalam Sub District Empat Lawang District and to study difference of earnings beetwen farmer of coffee using appliance of pulper coffe and farmer who using the way of traditional in Tangga Rasa Village Sikap Dalam Sub District Empat Lawang District. Location Research determined by purposive with consideration that the area there are effort processing of fruit coffe by pulper coffe tool. This research be executed in October to November 2014.Research method used survey method and withdrawal of example used Distriporpotionate Stratified Random Sampling. Result of research indicated that factors which farmer background use pulper coffe were price and earnings of coffe farmer using appliance of pulper coffe mean Rp. 16.433.697,40 per hectare per year. And earnings of farmer of coffee using the way of is traditional Rp. 11.691.238,48 per hectare per year. Price of coffee with pulper cofee processing equal to Rp 16.000,00 per kilogram, higher in comparison with price of processed coffee traditionally was Rp. 14.000,00 per kilogram.